A Memory Sharing based Low Loss Rate Data Gathering Algorithm with a Mobile Sink for Wireless Sensor and Actuator Networks. Issue 4 (16th November 2016) - Zhu, C.; Han, G.J.; Wang, Y.; Bao, P.; Shen, J.
Abstract: This paper exploits memory sharing among nodes and a proactively upload method to avoid data loss and improve the energy efficiency of network. A memory sharing low loss rate data gathering algorithm MSDGA is proposed. Based on K ‐hop spanning tree topology, MSDGA combines locally passive uploading and globally proactive uploading. On one hand, local data collection mode shortens the length of data routing, therefore the energy consumption of nodes is decreased and the network lifetime is prolonged. On the other hand, the whole network proactive transmission mode reduces the memory overflow ratio and packet loss ratio caused by beyond the validity period, which earns higher packets delivery ratio and acceptable data transmission delay. Extensive simulations show that compared with other algorithms, MSDGA has longer network lifetime, higher packets delivery ratio and acceptable data transmission delay.